Electroencephalographic Abnormalites in SARS-CoV-2 Patients - Besnard, Stephane; Nardin, Clotilde; Lyon, Elsa; Debroucker, Thomas; Arjmand, Roxana; Moretti, Raffaella; Pochat, Hervé (Frontiers in Neurology, 2020)
Viral infection with SARS-CoV-2 has a neurological tropism that may induce an encephalopathy. In this context, electroencephalographic exploration (EEG) is indicated as a diagnostic argument correlated with lumbar puncture, biology and imaging. We performed a retrospective analysis of 42 patients explored by EEG and infected by COVID-19, according to the EEG abnormalities and clinical signs that motivated the examination. Confusion and epileptic seizures were the most clinical indications with 64% of the patients. The EEG was altered in 85% of the cases of confusion, in 57% of cases of epileptic symptoms (general or focal seizure or prolonged loss of contact) and 20% of cases of malaise or brief loss of consciousness. Nine EEG (21%) were in favor of an encephalopathy, two had de novo alterations in persistent consciousness and two had alterations in general state with confusion; one was very agitated and without history of epilepsy and combined eyelids clonia while a second one exhibited unconsciouness with left hemicorpus clonus. Two were being investigated for delayed awakening without sedation for more than 24 hours. All of these patients were diagnosed COVID-19 with some of them associated mild to severe respiratory disorders. This work shows the interest of the EEG in exploring COVID-19 patient suffering from neurological or general symptoms looking for cerebral alteration.